A Microcontroller based remote engine starter and keyless entry using ZIGBEE with security system - Laiz, Lar Daniel S. (Animo Repository, 2009)
ZIGBEE is widely used in applications that involve monitoring and communicating functions. Most of the time, people use ZIGBEE in a fixed location system and communicate via serial communication. ZIGBEE has linking capabilities allowing multiple child ZIGBEEs or the end devices to communicate with the Parent ZIGBEE or the coordinator. This thesis uses ZIGBEE and its digital input / output capabilities to control several functions of automobile remotely. The ZIGBEE utilizes point-to-point communication similar to a remote control in car locks. The ZIGBEE is connected to a microcontroller which reads the digital input fed by the ZIGBEE receiver and performs a corresponding action for each signal inputted into the comparator pins of the microcontroller. The microcontroller send signals which controls several functions like lock, unlock and disarm of an alarm system, as well as a series of relays that controls the engine starter of an automobile. The user can control the activation of what normally requires the car keys to perform these functions include the accessories, the car's electrical such as the heater in diesel engines and the starter of the car. The purpose of this thesis is to look into the possibility of using ZIGBEE in automobile application, one of which is a remote engine starter and keyless entry.